2022
DOI: 10.24252/lp.2022v25n2i10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Story-Based Teaching Materials for Islamic Religious Education Courses

Abstract: The dissemination of the development of story-based teaching materials at the University of West Sulawesi was carried out with a 4D model. The data were obtained based on student learning outcomes and student and lecturer responses. The profile of teaching materials consists of: (a) basic competencies, (b) indicators, (c) objectives, (d) concept maps, (e) materials, equipped with stories of each subject, (f) formative tests, and ( g) bibliography. The effectiveness test was declared complete individually and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies have shown that storytelling, an ancient tradition to impart values and cultures, has been widely utilized to enhance students' language, cognition, and emotion and as part of a curriculum for teaching youth within an education environment (Iroh, 2022;Vinnikova, 2022;Connaughton et al, 2019;Hendrickson, 1992). For instance, researchers have discussed the validity of storytelling in teaching language to young learners (Piórkowska and Malenko, 2017), examined the dissemination and components of story-based teaching materials (Ondeng et al, 2022), and developed narrative text-based materials in a curriculum to stimulate students' interest, motivation, and vitalize teachers' teaching (Ningsih, 2022). However, as a double-edged sword, the richness of story resources challenges teachers' ability to choose and adapt teaching materials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that storytelling, an ancient tradition to impart values and cultures, has been widely utilized to enhance students' language, cognition, and emotion and as part of a curriculum for teaching youth within an education environment (Iroh, 2022;Vinnikova, 2022;Connaughton et al, 2019;Hendrickson, 1992). For instance, researchers have discussed the validity of storytelling in teaching language to young learners (Piórkowska and Malenko, 2017), examined the dissemination and components of story-based teaching materials (Ondeng et al, 2022), and developed narrative text-based materials in a curriculum to stimulate students' interest, motivation, and vitalize teachers' teaching (Ningsih, 2022). However, as a double-edged sword, the richness of story resources challenges teachers' ability to choose and adapt teaching materials.…”
Section: Introductionmentioning
confidence: 99%